Gift of Voice to Mute: Hand Gestures Converted to Text and Voice - Taneja, Seher; Sukhija, Mandeep (International Journal of Computer Sciences and Engineering, 2020)
Though Sign language using gestures and facial expressions helps deaf and dumb people to express their thoughts, normal people do not learn sign language and therefore not able to comprehend it thus causing a barrier between the two and a big cause of frustration. With the objective to lower the barrier in communication by opening up conversations between signers and speakers, we have converted sign language to text and speech using flex sensors, Arduino Uno, HC-05: Bluetooth and a mobile device as the hardware and Arduino IDE and MIT App Inventor as the software. Normal driving gloves have been converted to wireless data smart gloves by fitting them with flex sensors along the length of each finger and the thumb and accelero sensor. The signals are passed on Arduino Uno which converts analog signal from the sensors to digital signals. The signal is then passed on to a Bluetooth device HC-05.Then signal is transmitted to a mobile device on a Bluetooth app. Signal is then converted into a voice message. This low cost solution is affordable, portable and easily customizable with additional Feature for GPS location for safety purposes.